Plan de Marketing para la empresa PROVEMUEB LE de la ciudad de Loja - Gálvez Loja, Kevin Andrés (2024)
The objective of this research is to develop a “MARKETING PLAN FOR THE PROVEMUEBLE COMPANY OF THE CITY OF LOJA”, which leads to the growth and development of the company, which was based on four specific objectives. The first objective corresponds to carrying out an internal and external situational analysis and a competitive analysis to identify strengths, opportunities, weaknesses and threats that the company has, for the external diagnosis the PESTEC analysis was carried out which allowed determining the political, economic, social, technological, ecological, as well as a study of Porter's 5 forces which allowed us to have a clearer picture of the current situation of the company. For the internal diagnosis, the Internal Factors Matrix was constructed using the information obtained in the surveys, the interview and through direct observation, where a descriptive observational methodology was used, with a qualitative and quantitative approach, with a non-sampling technique. probabilistic by own judgment. Where a survey was applied to 284 clients. In addition, throughout this research process, strategic tools were applied, such as the Ansoff matrix, internal and external matrix and SWOT matrix to identify the key factors and the high impact matrix to determine the strategies. The second object is to define strategies through which the micro and macro strategies are developed. The third objective is to define the tactics and actions where the plan proposal was developed. The fourth objective focused on the preparation of the budget for the marketing plan, projecting a result of $1550. Finally, the conclusions and recommendations are presented, as well as the bibliography and annexes.